POLR3A-related syndrome complicated with cerebral abscesses: a case report and literature review - Zhou, Mengyao; Hou, Lingli; Fan, Huijuan; Duan, Yuanfang; Xie, Xinye; Wu, Haohao; Wang, Hanmin; Zhang, Wei; Du, Kang (Frontiers in Genetics, 2026)
BackgroundPOLR3A gene-related syndrome is a complex genetic disorder with diverse clinical manifestations. Understanding its characteristics is crucial for diagnosis and management. Previous studies have reported various aspects of this syndrome, yet a comprehensive analysis of different Variant sites and their associated phenotypes remains necessary.Case reportThis study presents a case of POLR3A-related syndrome in a pediatric patient. Symptom onset occurred after 2 years of age, initially presenting with gait disturbance. As the disease progressed, gait instability worsened progressively and was accompanied by dysarthria, intellectual developmental impairment, and tremor. Subsequent neuroimaging revealed multiple intracerebral infectious lesions with abscess formation. Whole-genome sequencing identified a homozygous c.1771-6C>G variant in the POLR3A gene. This variant has been previously reported as pathogenic at this locus; however, the complication of multiple intracerebral infections and abscess formation represents a previously unreported manifestation. It is noteworthy that the parents of the proband were consanguineous (first-degree relatives).ConclusionA review of 60 unrelated probands with POLR3A-related syndrome was conducted based on previously published cases. The analysis revealed no significant sex difference in disease occurrence. The median age of onset was approximately 8 years, with common initial symptoms including gait disturbance and cognitive developmental impairment. Neuroimaging findings indicated cerebral atrophy in 31 cases (66.0%) and white matter hypomyelination in 17 cases (34.7%). Among the reported genetic variants, c.1909 + 22G>A was the most prevalent, identified in 19 families (17.8%), followed by c.1771-6C>G in 9 families (6.4%). Furthermore, patients with different variant sites displayed heterogeneity in initial symptoms, clinical presentations, and imaging characteristics. This comprehensive review enhances the understanding of the phenotypic and genotypic spectrum of POLR3A-related syndrome.